The AGN fuelling/feedback cycle in nearby radio galaxies I. ALMA observations and early results. Issue 3 (23rd January 2019) - Ruffa, Ilaria; Prandoni, Isabella; Laing, Robert A; Paladino, Rosita; Parma, Paola; de Ruiter, Hans; Mignano, Arturo; Davis, Timothy A; Bureau, Martin; Warren, Joshua
Abstract: This is the first paper of a series exploring the multifrequency properties of a sample of 11 nearby low-excitation radio galaxies (LERGs) in the southern sky. We are conducting an extensive study of different galaxy components (stars, warm and cold gas, radio jets) with the aim of improving our understanding of the active galactic nucleus (AGN) fuelling/feedback cycle in LERGs. We present ALMA band 6 12 CO(2–1) and continuum observations of nine sources. Continuum emission from the radio cores was detected in all objects. Six sources also show mm emission from jets on kpc/sub-kpc scales. The jet structures are very similar at mm and cm wavelengths. We conclude that synchrotron emission associated with the radio jets dominates the continuum spectra up to 230 GHz. The 12 CO(2–1) line was detected in emission in six out of nine objects, with molecular gas masses ranging from 2 × 10 7 to 2 × 10 10 M⊙ . The CO detections show disc-like structures on scales from ≈0.2 to ≈10 kpc. In one case (NGC 3100) the CO disc presents some asymmetries and is disrupted in the direction of the northern radio jet, indicating a possible jet/disc interaction. In IC 4296, CO is detected in absorption against the radio core as well as in emission. In four of the six galaxies with CO detections, the gas rotation axes are roughly parallel to the radio jets in projection; the remaining two cases show large misalignments. In those objects where optical imaging is available, dust and CO appear to be co-spatial.